Analysisi of Factors Affecting The Poverty Rate In Central Java Province in 2018-2021 - Aji Kusuma, Fauzan; Hasmarini, Maulidyah Indira (CV. Publikasi Indonesia, 2023)
Poverty is one of the fundamental issues that is the center of the government's attention. Reducing the poverty rate is one of the Central Java government programs. By Therefore, it is necessary to know what factors can affect the poverty rate in Central Java. This study aims to analyze the influence of the human development index (HDI), gross regional domestic product (GRDP), population, unemployment rate, Government expenditure on the poverty rate in Central Java Province. This research uses data from 2018-2021 sourced from the central statistics agency (BPS) by using panel data regression using three models pooled least squares (PLS) models, fixed effect model (FEM), and random effect model (REM). The best model specification results is the fixed effect model (FEM). The results of this study indicate that the human development index has a negative and insignificant effect on the poverty rate, gross domestic product has a negative and insignificant effect on the poverty rate, population has a significant negative effect on the poverty rate, the unemployment rate has a negative and insignificant effect on the poverty rate, and government spending has a positive and insignificant effect on the poverty rate